Fetal Bovine Serum dalam Pengencer Tris Mempertahankan Kehidupan dan Keutuhan Membran Plasma Spermatozoa Semen Beku Domba Garut (FETAL BOVINE SERUM IN TRIS EXTENDER MAINTAINING SPERMATOZOA VIABILITY AND PLASMA MEMBRANE INTEGRITY OF GARUT RAM FROZEN SEMEN - Rizal, Muhammad; ., Herdis; Sangadji, Insun (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
The objective of this study was to examine the effectiveness of fetal bovine serum (FBS) against thequality of garut ram frozen semen. Semen was collected from one mature garut ram using artificial vagina.Fresh semen were evaluated then divided into four tubes at equal volume and each tube were diluted withTris extender containing 20% egg yolk (TEY-20, as control); TEY-20 + 8% FBS (FBS-8); TEY-20 + 10% FBS(FBS-10); and TEY-20 + 12% FBS (FBS-12), respectively. Semen at the concentration of 100x106 motilespermatozoa was loaded in 0.25 ml mini straw. Semen was equilibrated at 50C for three hours, then freezeand stored in liquid nitrogen container. The quality of the spermatozoa including percentages of motileand live spermatozoa, intact plasma membrane (IPM) were evaluated following diluting, equilibratingand thawing process. A Complete Randomized design using four treatments and five replicates were usedin the study. The results showed that there was no significant difference (p<0.05) in percentage of motilespermatozoa following thawing between the control (44.0%) and FBS-8 (46.0%), FBS-10 (48.0%), andFBS-12 (47.0%), respectively. The percentage of live spermatozoa and IPM were significantly higher (p<0.05)in the FBS-8 (69.0% and 58.2%); FBS-10 (72.4% and 61.2%); FBS-12 (72.2% and 64.4%) compared to thecontrol (64.8% and 52.8%), respectively. In conclusion, the addition of FBS into Tris extender was able tomaintain the viability and integrity of plasma membrane of garut ram frozen semen.
Keywords: fetal bovine serum (FBS), frozen semen, garut ram